On the piecewise approximation of bi Lipschitz curves - Pratelli, Aldo; Radici, Emanuela (2015)
In this paper we deal with the task of uniformly approximating an L-biLipschitz curve by means of piecewise linear ones. This is rather simple if one is satisfied to have approximating functions which are L-biLipschitz, for instance this was already done with L=4L in [Daneri-Pratelli, Lemma 5.5]. The main result of this paper is to do the same with L=L+ε (which is of course the best possible result); in the end, we generalize the result to the case of closed curves.